Working capital and firm performance in Sub-Saharan Africa: Emphasis on the moderating role of rule of law - Yeboah, Michael; Yeboah, Benjamin; Atuahene, Samuel O Owusu; Bawuah, Jonas (Asian Journal of Economic Modelling, 2024)
The study investigated the extent to which institutional quality affects the correlation between working capital and the performance of manufacturing enterprises listed in several sub-Saharan African nations. The study sourced information from certified financial accounts of the companies, World Development Indicators, 2021, and Global Governance Indicators covering the period from 2010 to 2020. We selected five consistently listed companies from Ghana, Nigeria, Mali, and Cote d’Ivoire. We measured institutional quality as a rule of law and used return on equity as an indicator of performance. The control variables for the study are firm size, leverage, interest cover, inflation, and foreign direct investment. The study used the Are-llano-Bond two-step GMM estimator to gauge the influence of working capital on return on equity while also examining the moderating effect of the rule of law on the connection between working capital and return on equity. Working capital has a statistically significant positive impact on equity returns. The rule of law significantly enhances the positive impact of working capital on equity returns. Sub-Saharan African countries should improve and build strong institutions where the rule of law is efficient and effective to pave the way for the sustainable performance of companies.